2015
DOI: 10.1159/000434748
|View full text |Cite
|
Sign up to set email alerts
|

An International Perspective on Quality of Life in Aphasia: A Survey of Clinician Views and Practices from Sixteen Countries

Abstract: Objective: To gain an insight into speech and language therapists' perspectives on and practices in quality of life in aphasia. Participants and Methods: The International Association of Logopedics and Phoniatrics Aphasia Committee developed a survey questionnaire, which was delivered online, anonymously, through SurveyMonkey (November 2012 to April 2013) to clinicians working with people with aphasia in 16 countries across the world. Results: A large number of speech and language therapists responded to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In clinical practice, it is important to have a broad understanding of the various areas in patients' lives that might have an impact on QoL. An assessment of QoL after stroke would offer a more holistic picture of stroke recovery from the patient's perspective [9,36]. Therefore, QoL assessment should be given greater attention in future research, especially in daily clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is important to have a broad understanding of the various areas in patients' lives that might have an impact on QoL. An assessment of QoL after stroke would offer a more holistic picture of stroke recovery from the patient's perspective [9,36]. Therefore, QoL assessment should be given greater attention in future research, especially in daily clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the current practices and beliefs of SLTs, a recent international survey ( n = 579) found that 74% of SLTs considered quality of life to be the main aim of aphasia rehabilitation (Hilari et al . ). In the UK, Brumfitt () found that 97% of SLTs ( n = 173) stated that psychosocial aspects were important or very important to their management of clients with aphasia; while an Australian survey found that 98% of SLTs ( n = 111) felt they had a role to play in addressing psychological well‐being (Sekhon et al .…”
Section: Introductionmentioning
confidence: 97%
“…Despite the known prevalence and substantial impact of aphasia on the lives of PWA, a study conducted by Hilari et al . () into speech–language pathologists’ (SLPs) perspectives of QoL for PWA across 16 countries found that QoL outcomes measures are not routinely used in clinical practice. The main recommendation from this study was that health professionals (HPs) need education and training to ensure consideration of such measures for use with PWA.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, it is hoped that PWA will continue to live successfully with aphasia as the perceived health‐related QoL outcomes impacted by aphasia can be addressed (Hilari et al . , ).…”
Section: Introductionmentioning
confidence: 99%